Heulandite/polyaniline hybrid composite for efficient removal of acidic dye from water; kinetic, equilibrium studies and statistical optimization; Advanced Powder Technology; Vol. 29, iss. 10 - Abukhadra M. R. Mostafa; Rabia M. Mohamed; Shaban M. Mohamed; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen